How do young women approaching screening age interpret the NHS cervical screening leaflet? A mixed methods study of identifying interpretation difficulties, barriers, facilitators, and leaflet interpretation, engagement and future screening behaviour - Caroline Charlton; Angela M. Rodrigues (Health Psychology and Behavioral Medicine)
Background: Cervical cancer is a common cancer among young women aged 25–29 in England, and the NHS cervical screening leaflet is the first point of contact for those being invited for their first screening. This study aimed to explore how young women (18–24) understand and engage with the leaflet, as well as the barriers and facilitators associated with its interpretation, engagement, and screening intentions. Methods: The study used a mixed-methods approach, including a survey (n = 120) to identify interpretation difficulties and how they were affected by different characteristics, and a follow-up interview (n = 10) to assess the utility of the leaflet, identify issues with its practicality, and determine the factors that influence screening intentions. Results: The survey results showed that interpretation difficulties were common, particularly regarding HPV assessment, screening results, additional tests/treatment, and screening risks. Lower interpretation accuracy was associated with lower numeracy scores and non-white ethnicity. Despite these difficulties, participants had high confidence and motivation to engage with the leaflet. The interviews revealed knowledge gaps, issues with the leaflet's practicality, and a preference for digital information. Factors that were identified as barriers and facilitators of leaflet interpretation, engagement, and screening intentions included knowledge, social influence, beliefs about consequences, environmental context and resources, social role and identity, emotions and intentions. Conclusion: The current leaflet does not provide enough information for young women to make an informed decision about screening attendance. Implementing a digital invitation featuring simplified gist representation, targeted behaviour change techniques (BCTs), videos, and interactive tools can enhance education and promote screening behaviour. Future research should consider using digital tools and strategies to address existing barriers related to interpretation and engagement.